Increase of austenitic ductile iron type D5S durability by high temperature pre-treatment - Nowak W.J.; Wierzba B.; Mazurkow A.; Jaworski A.; Krawczyk Ł. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present work, a performance of ASTM A439 Austenitic Ductile Iron type D5S at high temperature in the oxidizing environment was investigated. The obtained results revealed that exposure at temperatures 800°C, 850°C, and 900°C resulted in relatively high mass gain and an extensive oxide scale spallation from the samples’ surfaces during cooling. However, the material exposed at 950°C revealed a better oxidation resistance and no oxide scale spallation. The material exposed at 1000°C showed the best oxidation resistance among the studied samples. The surfaces and cross-sectional investigation revealed that the material exposed at 950°C formed mostly Ni/Cr/Mn-mixed protective oxide scale and local formation of Fe-rich nodules. In comparison with the sample exposed at 1000°C, a smaller amount of Fe-rich nodules per area unit was observed and most of the surface was covered by Ni/Cr/Mn-mixed protective scale. The latter was explained by the change in the calculated diffusion coefficients in the alloy for Ni and Fe, namely up to 900°C the diffusion coefficient for Fe was much higher than for Ni, while above 900°C the diffusion coefficient for Ni becomes higher than for Fe. This phenomenon was correlated with a phase transformation from α-Fe into γ-Fe resulting in the diffusion coefficient change.